Prevalence and associated factors of mental health concerns among basic education teachers during COVID-19 pandemic - Imelu Mordeno; Lowell Lucero; Jimayma Bigcas (Frontiers in Education, 2026)
Aims While research on the effects of the COVID-19 pandemic is growing, studies on its impact on basic education teachers’ mental health, especially in a low-to-middle-income, Southeast Asian context, are limited. To address this gap, the present study investigated the estimated prevalence and risk factors of mental health problems (i.e., psychological distress, generalized anxiety, and major depression) among Filipino basic education teachers during the pandemic. Methods A cross-sectional study was conducted among 1,992 Filipino basic education teachers. Relevant instruments were used to assess pandemic-related adversities, psychological distress, generalized anxiety, and major depression. Descriptive statistics were used to estimate the prevalence of mental health symptoms, while multiple logistic regression analyses identified independent risk factors after adjusting for age, sex, relationship status, educational level, and length of service. Model robustness was evaluated using goodness-of-fit, multicollinearity, and bootstrap analyses, with statistical significance set at p < .05. Results The prevalence of psychological distress, major depression, and generalized anxiety was 49.80%, 23.29%, and 17.17%, respectively. In terms of the demographic characteristics, younger teachers (≤35 years), those who were single, and those in the early years of their teaching career were at risk for psychological distress, major depression, and generalized anxiety. With regard to pandemic-related adversities, difficulty managing time and reduced social interaction, consistently predicted generalized anxiety, depression, and psychological distress. These findings demonstrate that both personal characteristics and pandemic-related stressors independently contributed to teachers’ mental health vulnerability. Conclusion This study provides one of the largest empirical assessments of teachers’ mental health conducted in the Philippines during the COVID-19 pandemic. The findings identify distinct demographic and pandemic-related risk factors that can guide the development of targeted mental health screening, prevention, and intervention strategies for vulnerable teacher subgroups. They also provide evidence to inform educational and public health policies aimed at strengthening psychological support systems and workforce resilience during future public health emergencies.